Solvent effect on the synthesis of monodisperse amine-capped Au nanoparticles - Wu, Bing-Hui; Yang, Hua-Yan; Huang, Hua-Qi; Chen, Guang-Xu; Zheng, Nan-Feng (Chinese chemical letters, 2013)
A remarkable solvent effect in a single-phase synthesis of monodisperse amine-capped Au nanoparticles is demonstrated.Oleylamine-capped Au nanoparticles were prepared via the reduction of HAuCU by an amine-borane complex in the presence of oleylamine in an organic solvent.When linear or planar hydrocarbon（e.g.,n-hexane,n-octane,1-octadecylene,benzene,and toluene） was used as the solvent, high-quality monodisperse Au nanoparticles with tunable sizes were obtained.However,Au nanoparticles with poor size dispersity were obtained when tetralin,chloroform or cyclohexane was used as the solvent.The revealed solvent effect allows the controlled synthesis of monodisperse Au nanoparticles with tunable size of 3-10 nm.